1991
DOI: 10.3758/bf03334754
|View full text |Cite
|
Sign up to set email alerts
|

Trait actualization and self-reference effects

Abstract: Subjects made self-reference judgments about the same trait adjectives from two perspectives, once in terms of the real self and once in terms of the ideal self. Traits could then be partitioned into four categories: those descriptive of both real-and ideal-self concepts, descriptive of real self only (not in the ideal-self concept), descriptive of ideal self only (not in the real-self concept), and those in neither the real-nor the ideal-self concept. Unactualized traits (real only or ideal only) took more ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Cronbach's alphas for independence and interdependence were r ¼ 0.79 and 0.80, respectively (Watson & Quatman, 2005). Following standard procedures for the selfreference effect (Mueller & Grove, 1991;Wagar & Cohen, 2003), we presented these adjectives randomly on a Dell Dimension laptop using Media Lab software to assess response latencies to independent (e.g., assertive, independent, self-reliant) and interdependent (e.g., compassionate, loyal, adaptable) traits or adjectives. Two control words (peaceful and tired) were always presented first as ''warm-ups'' and were not included in the analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Cronbach's alphas for independence and interdependence were r ¼ 0.79 and 0.80, respectively (Watson & Quatman, 2005). Following standard procedures for the selfreference effect (Mueller & Grove, 1991;Wagar & Cohen, 2003), we presented these adjectives randomly on a Dell Dimension laptop using Media Lab software to assess response latencies to independent (e.g., assertive, independent, self-reliant) and interdependent (e.g., compassionate, loyal, adaptable) traits or adjectives. Two control words (peaceful and tired) were always presented first as ''warm-ups'' and were not included in the analyses.…”
Section: Methodsmentioning
confidence: 99%
“…19, p < .01; Cacioppo & Petty, 1982), introspectiveness (r =. 16, p < .05; Berzonsky & Sullivan, 1992), desire for control (r = .48, p < .001; E. P. Thompson, Chaiken, & Hazlewood, 1993), need to evaluate (r = .35, p < .05; , self-directed religious problem-solving style (r = .25, p < .05; Tolentino et al, 1990), masculinity (but not femininity or androgeny; rs = .34 to .38, ps < .05; Osberg, 1987;Waters & Zakrajsek, 1990), self-esteem (meta-analysis ra,~ = .38, p < .001; Kernis et al, 1992;Mueller & Grove, 1991;Osberg, 1987;, total sensation seeking (rs =. 19 to .25, ps < .05; Crow-ley& Hoyer, 1989;Olson et al, 1984), communication apprehension (high scores reflect low apprehension; r = .33, p < .05; Wycoff, 1992 ), and inner directedness (inner-other social preference, r = .19, p < .05' [Crowley & Hoyer, 1989]; internalexternal correspondence, r = .12, p < .05 [Ickes & Teng,t987 ]).…”
Section: Predictive Validity and Personology: Beyond Cognitive Abilitymentioning
confidence: 99%
“…19 to .25, ps < .05; Crow-ley& Hoyer, 1989;Olson et al, 1984), communication apprehension (high scores reflect low apprehension; r = .33, p < .05; Wycoff, 1992 ), and inner directedness (inner-other social preference, r = .19, p < .05' [Crowley & Hoyer, 1989]; internalexternal correspondence, r = .12, p < .05 [Ickes & Teng,t987 ]). Individuals high in need for cognition also tend to be low in neuroticism (r = -.24, p < .05; Dornic et al, 1991 ), external locus of control (r = -.32, p < .05; Fletcher et al, 1986), and social anxiety (meta-analysis rave = -.35, p < .01; Mueller & Grove, 1991;Mueller et al, 1988;Mueller & Johnson, 1990;Osberg, 1987;, although the association with social anxiety is possibly heightened in elderly people (r = -.62, p < .01; Mueller & Johnson, 1990).…”
Section: Predictive Validity and Personology: Beyond Cognitive Abilitymentioning
confidence: 99%
“…followed by an adjective (e.g., humble), to which the subject must answer yes or no by pressing a button. Self is always one of the targets (though actual self and ideal self can be rated as separate targets, e.g., Mueller & Grove, 1991), and other typical targets can vary along dimensions of familiarity and intimacy. A highly familiar target of high intimacy might be mother or best friend; a highly familiar target of low intimacy could be a contemporary figure with a high media profile (such as Tony Blair or David Beckham); and an unfamiliar target, necessarily of low intimacy, might be the experimenter.…”
Section: Memory Biasesmentioning
confidence: 99%
“…Non-depressives can also show biases in memory toward negative self-referent content under certain conditions. Mueller and Grove (1991), for example, asked participants to make trait-word decisions for both actual self and ideal self, thereby presumably making discrepancies salient (cf. Higgins et al, 1997); they found that participants had better recall for undesirable trait words descriptive of actual self and for desirable trait words descriptive of ideal self.…”
Section: Summarizementioning
confidence: 99%